effects of Computer Aided Instruction Technique on academic performance and retention OF technical drawing students in technical college in anambra state: effects of Computer Aided Instruction Technique on academic performance and retention OF technical drawing students in technical college in anambra state (NAU Journal of Technology and Vocational Education, 2024)
The apparent decline in the performance of students in technical drawing examinations in Technical Colleges in Anambra State necessitated the study. Among other susceptible factors, the use of inappropriate teaching methods appears more crucial. Hence, the study investigated the effects of Computer Aided Instruction on Academic Performance and Retention of students in technical drawing in Government Technical Colleges in Anambra State. The study adopted a non-randomized quasi-experimental research design guided by two research questions and two hypotheses tested at 0.05 level of significance. The population was 537 National Technical College II (NTC II) students offering technical drawing with a sample size of 235. Purposive sampling technique was used to select four intact classes in technical colleges from different Local Government Areas of the State. The instrument for data collection was Technical Drawing Performance Test (TDPT) which contained 38 multiple choice items and two hands-on activity items. Three experts validated the instrument and its reliability coefficient was 0.83 which obtained using Chronbach Alpha. The research questions were analyzed using Mean while Analysis of Covariance (ANCOVA) was used to test the null hypotheses at 0.05 level of significance. Both experimental and control groups were pre-tested and taught by their regular teachers for four weeks using the lesson plans prepared by the researcher. A post-test was administered after teaching followed by a delayed post-test to ascertain their retention ability. The findings revealed among others, that computer aided instruction technique had more effect on students’ academic performance and retention with higher post-test mean scores than those taught with conventional method. Based on the findings, it was concluded that computer aided instruction technique could enhance students’ academic performance and retention in technical drawing. Hence, it was recommended among others that technical drawing teachers should embrace computer aided instruction technique to enable students learn actively and retain concepts for improved academic performance. Also, Government should in addition of providing ICT gadgets to school, support them in organizing seminars and workshops to train and retrain technical drawing teachers on how to effectively use CAI.
Keywords: Computer aided instruction; Technique; Technical college students; Academic performance; Retention; Technical drawing